Bilateral adrenal hemorrhage in polycythemia vera - Shruti Bhandari; Katrina Agito; Esther I. Krug (Greater Baltimore Medical Center, 2016)
Bilateral adrenal hemorrhage (BAH) is a rare complication typically seen in critically ill patients, which can lead to acute adrenal insufficiency and death unless it is recognized promptly and treated appropriately. We describe the case of a 64-year-old man with polycythemia vera found to be unresponsive with fever, hypotension, tachycardia, and hypoglycemia. Electrocardiogram showed ST-elevation with elevated troponin, hemoglobin, prothrombin time, and partial thromboplastin time. He required aggressive ventilator and vasopressor support. Despite primary coronary intervention, he remained hypotensive. Random cortisol level was low. He received stress dose hydrocortisone with immediate hemodynamic stability. BAH was highly suspected and was confirmed by non-contrast abdominal computed tomography. Prompt recognition and timely initiated treatment remain crucial to impact the mortality associated with acute adrenal insufficiency.